Development of E-Library Applications for Sociology Learning - Szauli Putra, Berkah Adityo (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
The background of this study is the lack of learning resources owned by students during the sociology learning process. The purpose of this study is to produce a feasible and practical E-Library application for learning Sociology. The type of research used in this research is Research and Development (R&D). The development model used in this development research is the ADDIE development model. The research instruments used included: validation sheets and practicality questionnaires. Data collection techniques are carried out using observation, tests, questionnaires, and documentation. The results showed that the media validation test for the media expert's assessment of the E-Library 1 application was 96% "very feasible", and the media expert's assessment 2 of the E-Library application was 95% "very feasible". The final score of the eligibility validation of media experts is 95.5% so the E-Library application for sociology learning is "very feasible" to use. Meanwhile, the material validation test for material expert 1's assessment of the E-Library application was 93% "very feasible", and material expert 2's assessment of the E-Library application was 87% "very feasible". The final score of the material expert feasibility validation is 90% so the E-Library application for sociology learning is "very feasible" to use. Furthermore, the results of the particulate test by students were 92%, and the value was categorized as "very practical". Based on this assessment, it can be concluded that the E-Library application for sociology learning has received good responses from users so that it is practically used in a learning process.